KIS: an automated attribute induction method for classification of DNA sequences - Biedrzycki, Rafał; Arabas, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an application of methods from the machine learning domain to solving the task of DNA sequence recognition. We present an algorithm that learns to recognize groups of DNA sequences sharing common features such as sequence functionality. We demonstrate application of the algorithm to find splice sites, i.e., to properly detect donor and acceptor sequences
Keywords: classification; optimization; annotation; patterns